Effect of ion chelator on hydration process of Portland cement. (30th October 2020) - Wang, Ruiyang; Yu, Jianying; Gu, Shunjie; Han, Xiaobin; He, Peng; Liu, Quantao; Xue, Lihui
Highlights: The addition of ion chelator accelerated the hydration of the cement paste. Incorporation of ion chelator in cement paste greatly improved the compressive strength. The ion chelator can effectively improve the pore structure and microstructure of cement paste. Abstract: Ion chelator is a novel crystalline additive which can chelate Ca 2+ and migrate in concrete to promote self-healing of surface crack and internal pore. In order to further explore the effect of ion chelator on hydration process of cement, the hydration heat, chemically bound water, compressive strength, hydration products, pore-size distribution and microstructure of cement paste with ion chelator were investigated in this paper. Results of the experiments showed that the ion chelator accelerated the hydration of the cement paste. Incorporation of ion chelator in cement greatly enhanced the chemically bound water content and the mechanical property. Compared with control cement paste, the chemically bound water content and compressive strength of cement paste with 0.5 wt% ion chelator increased by 13.3% and 16.8% after curing for 28 days. According to the DTA-TG and XRD tests, the ion chelator can promote the hydration of C3 S and C2 S, which was conducive to the generation of calcium silicate hydrate gels. Furthermore, the addition of ion chelator improved the pore-size distribution and microstructure of cement paste, and a large number of floccules and needles appeared in the pores of cement paste.